Goal clarity on the relationship between government ownership and financial performance of the listed companies in Kenya and Tanzania - Musa P. Ngilisho; Neema G. Mori; Ernest G. Kitindi (Cogent Business & Management, 2022)
This study investigates the moderating effect of company goal clarity on the relationship between government ownership and financial performance of the listed companies in Kenya and Tanzania. The results show that government ownership holds an average of 6% of the ownership stakes and a maximum of 74% in the selected listed companies. Furthermore, it is found that, listed companies that engage in goal-setting, pursue an average of 5 company goals concurrently, and a maximum of 13. Moreover, government ownership is found to be negatively related to financial performance, while a decrease in company goal clarity is both positively and negatively related to financial performance, for the Tobin's q and the risk-adjusted ROA models, respectively. The implication is that, as government ownership in emerging economies is endowed with relatively more skills and resources compared to other owners in listed companies, it can effectively pursue a relatively higher number of company goals. The results also suggest that a decrease in goal clarity has a negative moderating effect on the relationship between government ownership and financial performance, whereby the moderating effect reduces the magnitude of the negative effects of government ownership on financial performance, up to an optimal point of seven company goals. The decrease of company goal clarity, which mainly emanates from the concurrent pursuit of all company goals plus the social welfare ones, reduces the negative effects of the ownership on financial performances, contrary to the assertions made in the goal-setting theory.
Keywords: 650; financial performance; goal ambiguity; goal clarity; goal-setting; government ownership